2009
DOI: 10.1111/j.1471-4159.2009.06394.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane as an inducer of glutathione prevents oxidative stress‐induced cell death in a dopaminergic‐like neuroblastoma cell line

Abstract: The total GSH depletion observed in the substantia nigra (SN) appears to be responsible for subsequent oxidative stress (OS), mitochondrial dysfunction, and dopaminergic cell loss in patients with Parkinson’s disease. A strategy to prevent the OS of dopaminergic cells in the SN may be the use of chemopreventive agents as inducers of endogenous GSH, antioxidant and phase 2 enzymes. In this study, we demonstrated that treatment of the dopaminergic‐like neuroblastoma SH‐SY5Y cell line with sulforaphane (SF), a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…SF is a known activator of the Nrf2-ARE pathway. It has been reported that SF protects against 6-OHDA-induced oxidative stress by increasing the levels of GSH, NAD(P)H: quinine oxidoreductase-1, GSH-transferase and reductase (23). Whether HO-1 is involved in the SF-mediated protection against 6-OHDA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SF is a known activator of the Nrf2-ARE pathway. It has been reported that SF protects against 6-OHDA-induced oxidative stress by increasing the levels of GSH, NAD(P)H: quinine oxidoreductase-1, GSH-transferase and reductase (23). Whether HO-1 is involved in the SF-mediated protection against 6-OHDA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…SF also has been reported to be a potential candidate for development of treatment and/or prevention of PD (22). SF protects dopaminergic neurons against 6-OHDA-induced cytotoxicity (23,24). However, the molecular mechanisms by which SF protects against 6-OHDA-induced cytotoxicity are poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…SF is known to have cytoprotective effects by activating the transcription factor, NF-E2-related factor-2 (Nrf2), which binds to the anti-oxidant response element in the promoter region of a number of genes encoding anti-oxidative and phase 2 enzymes, including heme oxygenase-1, glutathione reductase and NAD(P)H:quinoine oxidoreductase 1 (17)(18)(19). SF first gained attention due to its potential as an anticancer agent (20).…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse cytotoxin (malonate) model of Huntington's disease, neuroprotection is observed by intrastriatal implantation of astrocytes with activated Nrf2-mediated gene expression [77]. Pretreatment of either dopaminergic cell lines or nigrostriatal co-cultures with sulforaphane provides neuroprotection against Parkinson's disease neurotoxins, e.g., 6-hydroxydopamine [78,79]. Mechanisms of neuroprotection in these models may include the increased expression of NQO1, which prevents ROS production that is catalyzed by the semiquinone fraction of the increased pool of quinones generated by aberrant dopamine metabolism, and increased levels of glutathione GSH, which detoxify peroxides and protect against oxidation of protein sulfhydryl groups [79].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Pretreatment of either dopaminergic cell lines or nigrostriatal co-cultures with sulforaphane provides neuroprotection against Parkinson's disease neurotoxins, e.g., 6-hydroxydopamine [78,79]. Mechanisms of neuroprotection in these models may include the increased expression of NQO1, which prevents ROS production that is catalyzed by the semiquinone fraction of the increased pool of quinones generated by aberrant dopamine metabolism, and increased levels of glutathione GSH, which detoxify peroxides and protect against oxidation of protein sulfhydryl groups [79]. In a MPTP mouse model of Parkinson's disease, overexpression of Nrf2 in astrocytes prevents neuronal death and reduces inflammation [80].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%